Exploring new frontiers in prostate cancer research: Report from the 2022 Coffey−Holden prostate cancer academy meeting. Issue 3 (28th November 2022) - Miyahira, Andrea K.; Hawley, Jessica E.; Adelaiye‐Ogala, Remi; Calais, Jeremie; Nappi, Lucia; Parikh, Ravi; Seibert, Tyler M.; Wasmuth, Elizabeth V.; Wei, Xiao X.; Pienta, Kenneth J.; Soule, Howard R.
Abstract: Introduction: The 2022 Coffey−Holden Prostate Cancer Academy (CHPCA) Meeting, "Exploring New Frontiers in Prostate Cancer Research, " was held from June 23 to 26, 2022, at the University of California, Los Angeles, Luskin Conference Center, in Los Angeles, CA. Methods: The CHPCA Meeting is an annual discussion‐oriented scientific conference organized by the Prostate Cancer Foundation, that focuses on emerging and next‐step topics deemed critical for making the next major advances in prostate cancer research and clinical care. The 2022 CHPCA Meeting included 35 talks over 10 sessions and was attended by 73 academic investigators. Results: Major topic areas discussed at the meeting included: prostate cancer diversity and disparities, the impact of social determinants on research and patient outcomes, leveraging real‐world and retrospective data, development of artificial intelligence biomarkers, androgen receptor (AR) signaling biology and new strategies for targeting AR, features of homologous recombination deficient prostate cancer, and future directions in immunotherapy and nuclear theranostics. Discussion: This article summarizes the scientific presentations from the 2022 CHPCA Meeting, with the goal that dissemination of this knowledge will contribute to furthering global prostate cancer research efforts.